Baldassarre Longhena's funerary monument to Doge Giovanni Pesaro. Issue 1 (2nd January 2019) - Colombo, Stefano
Abstract: This article investigates Baldassarre Longhena's funerary monument to Doge Giovanni Pesaro (Venice, 1669) and its late seventeenth-century description and reception in Giovanni Prati's panegyric ekphrasis (published 1690). By imagining a seventeenth-century viewer marvelling at the monument, Prati's epideictic description reinvents the sculptures of the monument, giving praise to the sculptor's ability to infuse crude stone with tangible life. By using visual metaphors which excite a vivid picture of the monument before the viewer's eyes, Prati's poem confers on his description a brilliance that results in the illusion of life. Likewise, the lifelikeness of the sculptures of the monument, enlivened by the eloquence of Prati's words, results in an image which appears alive and persuasive. As a whole, the comparative analysis of Prati's poem and the Pesaro monument sheds new light on how the mutual interaction between verbal and visual languages enhanced seventeenth-century viewers' experience by eliciting a response of an intellectual and emotional nature. It contributes to the reconsideration of the dynamic relationship between the poem, the monument, and their audiences.